IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DAN PENGARUHNYA TERHADAP PENINGKATAN MUTU SEKOLAH DASAR DI KECAMATAN KOTA TAMBOLAKA SUMBA BARAT DAYA - NTT - Mikael Sene; Elyakim Nova Supriyedi Patty (SekolahTinggi Keguruan dan Ilmu Pendidikan (STKIP), 2017)
This research entitled “Implementation of School-based Management and its impact on improving the quality of schools in District of Tambolaka City, Southwest Sumba, East NusaTenggara. This research was conducted in Southwest Sumba, East Nusa Tenggara. The purpose of this research is to know the implementation of school-based management has an influence onthe improvement of the quality of primary school in Tambolaka City District, Southwest Sumba, East Nusa Tenggara. This research is a type of correlational research. This research uses design: Ex post facto, using factual data. The sample is determined by proportional random sampling technique. Research pupulation is all teachers of primary school with a sample of 50 teachers from 10 primary schools. Data is collected by using questionnaire. Validity testing of research points is conducted by using contruct validity, and reliability testing by using Alpha-Cronbach method. Data analysis using descriptive analysis technique and simple linear regression. The result of research indicates that 1) implementation of school-based management in sub-district of Tambolaka city is in excellent category is about 64% and proper category is about 36%. This data shows that implementation of school-based management in all primary schools of Tambolaka district is averagely excellent. 2) The quality of primary schools in Tambolaka district reaching 70% is in proper category, 20% is in moderate category, and 2 % is in theminus category. 3) Based on the result of regression analysis, it can be obtained the significance value of the MBS to the quality of schools is about 0,09 or (p smaller than 0,05). It means, MBS regression analysis to the school quality is significant. Therefore, Ha is approved or Ho is rejected. Thus, it can be concluded that there is a significant influence between MBS variable to the school quality. Based on the result of regression analysis, it can be obtained the coeficient of determination (R2) is about 0,134. It means that the influence of MBS to the school quality is about 0,134 or 13,4%. This research is also influenced by other factors.